Analisis Posisi Kepuasan Konsumen Dan Faktor-Faktor Yang Mempengaruhinya (Studi Kasus Pada Restoran Kentucky Fried Chicken Galeria Mall, Yogyakarta) - Indah Widowati; Antik Suprihanti; Hernawa Ardityas Fitrawati (Jurnal Dinamika Sosial Ekonomi, 2009)
Analysis of Costumer Satisfaction Position and It’s Influenced Factors (a Case Study on Kentucky Fried Chicken Restaurant Galeria Mall, Yogyakarta. Supervised by and This research aims lo analyze the costumer satisfaction position of KFC Restaurant Galeria Mall, Yogyakarta and to analyze the influence of product, place, promotion, human resources, physical facilities, and the process to customer satisfaction of KFC Restaurant Galeria Mall Yogfakarta. Data obtained from interviews, observation, recording, and questionnaires sample with I00 respondents, Sampling method using non-probability sampling, and analisys techniques using likert scale, cartesius diagram and regression. The results of this research are the consumer satisfaction position of Kentucky Fried Chicken restaurant Galeria mall, Yogyakarta is located at the position "Pertahankan Prestasi (kuadran B)."The influence of marketing to the customer satisfaction of restaurant Galeria Mall, Yogyakarta.Key word: product, place, promotion, human resources.